The Development of a self-contained community a case study of Barangay Pulung Maragul, Angeles City, Philippines - Najian, Hamid 1957- (1988)
Pulung Maragul is a case study wherein the results could be utilized by the community and applicable to the development of other communities in Angeles City based on the concept of self-help or self-containment. Hence, these recommendations could be implemented as a development guideline not only for Pulung Maragul community and other communities sorrounding it but aslo by communities which have similar objectives and characteristics. The planning and design process has been the major guideline and policy in developing community. Christaller's theory and the hexagonal configuration of the clusters are highly recommended since this hexagonal packing with each being tangential to the other is mathematically the most efficient system. The heaxagonal shape of clusters fosters a sense of security and fence for the community. A mixed type of housing with different sizes of the plots is suggested for the individuality of people varying in interests and budgets. Residential houses could be disigned on a wide lot horizontally. Commercial and residential houses would be designed on smaller lots. Due to similarity of the barangays and neighborhood and barangay as for instance, ( 12 N6 - B7) Lot 12, Neighborhood 6, Barangay 7, Pulung Maragul. Therefore, proper signs and directions should be installed for easy access. Streets are designed on the periphery of the barangay, therefore, no street is found inside the community, the non-conventional street pattern is aimed at reducing vehice speed at intesections. The community is basically pdestrain-oriented. A bicycle trail system along the streets and pedestrian paths in the community. The bikeway network fosters a fast, economical and easy movement within the community. This system attracts the bicycle industries in the community and provides more job opportunities for the community. Aesthetics in the community is not an afterthought. It is a necessity. The community should be properly landscaped and organized. Any city planning worthy to be called organic must bring some measure of beauty and order into the poorest neighborhood. The maintenance of the landscape and the organization of each unit or cluster is the responsibility of its residents. Each unit is represented by the unit head who organizes the unit he lives in. The cooperation of each cluster is needed to improve their own community. Here is where citizen participation is highly recommended. This can be enhanced by provision of incentives for the residents.Solar energy utilization is very much suited in a self-contained community. Its use is practical and economically acceptable as an alternative to the ever-increasing proces of fuel, gas and electricity. Proper installation and introduction by residents of solar energy will help greatly improve the community economy. Pulung Maragul community is proposed to be developed through a phased schedule. The need to uplift the local economy as a priority for this particular community calls for the development and construction of industrial and commercial areas first. This study which was carried through to the end with the combined efforts of the author and the wonderful residents of Pulung Maragul came out with the said recommendations which the author believes will help the Pulung Maragul community attain self-containment and prosperity.
Vita.
Thesis (Master of Architecture : Community Architecture)--University of the Philippines, Diliman.
Keywords: Community development -- Barangay Pulung Maragul (Angeles City)